2009
DOI: 10.1021/bi801857t
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Refolding of Protein Domains and Subunits: Example of the Dimeric Two-Domain 3-Isopropylmalate Dehydrogenases

Abstract: The refolding mechanism of the homodimeric two-domain 3-isopropylmalate dehydrogenase (IPMDH) from the organisms adapted to different temperatures, Thermus thermophilus (Tt), Escherichia coli (Ec), and Vibrio sp. I5 (Vib), is described. In all three cases, instead of a self-template mechanism, the high extent of symmetry and cooperativity in folding of subunits and domains have been concluded from the following experimental findings: The complex time course of refolding, monitored by Trp fluorescence, consists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…This can explain the lower k cat values. In several other cases, tagged enzymes were used for kinetic measurements (49,50), which may have resulted in enzyme instability or interference with catalysis (51). We also found a few cases where enzymes were refolded from aggregated protein (52), suggesting that the measurement buffer might contain misfolded enzyme and, therefore, underestimate k cat .…”
Section: Discussionmentioning
confidence: 93%
“…This can explain the lower k cat values. In several other cases, tagged enzymes were used for kinetic measurements (49,50), which may have resulted in enzyme instability or interference with catalysis (51). We also found a few cases where enzymes were refolded from aggregated protein (52), suggesting that the measurement buffer might contain misfolded enzyme and, therefore, underestimate k cat .…”
Section: Discussionmentioning
confidence: 93%
“…E270 of Tt ‐IPMDH was mutated into Ala using the QuickChange site‐directed mutagenesis kit. The modified enzyme was expressed and purified using the previously published method applied for the wild‐type enzyme [8]. The enzyme (about 30 mg/ml) was obtained in a 25 mM MOPS/KOH buffer, pH 7.6 and then lyophilised.…”
Section: Methodsmentioning
confidence: 99%
“…Abbreviations: IPMDH, 3-isopropylmalate dehydrogenase (EC 1.1.1.85); Tt, Thermus thermophilus; IPM, (2R,3S)-3-isopropylmalate; MOPS, 3-(N-morpholino)propane-sulphonic acid; SAXS, small angle X-ray scattering; FRET, fluorescence resonance energy transfer and purified using the previously published method applied for the wild-type enzyme [8]. The enzyme (about 30 mg/ml) was obtained in a 25 mM MOPS/KOH buffer, pH 7.6 and then lyophilised.…”
Section: Enzymes and Chemicalsmentioning
confidence: 99%
“…From mutational studies with the Tt enzyme W77 and W195 could be identified as the participants in the FRET process. A reasonable structural explanation has been also provided: it was concluded that while the FRET signal of W77 reports on formation of the domain-closed conformation, that of W195 reports on the structural changes occurring at both subunit-subunit and domain-domain interfaces upon binding of IPM [8]. It is possible that the same type of mechanisms operate also in case of Ec enzyme where the equivalent side-chains are W81 and W205 [17].…”
Section: The Metal-ion Dependence Of the Fret Phenomenonmentioning
confidence: 95%